Emerging Trends in Lipid-Based Vaccine Delivery: A Special Focus on Developmental Strategies, Fabrication Methods, and Applications - Bharathi Karunakaran; Raghav Gupta; Pranav Patel; Sagar Salave; Amit Sharma; Dhruv Desai; Derajram Benival; Nagavendra Kommineni (Vaccines, 2023)
Lipid-based vaccine delivery systems such as the conventional liposomes, virosomes, bilosomes, vesosomes, pH-fusogenic liposomes, transferosomes, immuno-liposomes, ethosomes, and lipid nanoparticles have gained a remarkable interest in vaccine delivery due to their ability to render antigens in vesicular structures, that in turn prevents its enzymatic degradation in vivo. The particulate form of lipid-based nanocarriers confers immunostimulatory potential, making them ideal antigen carriers. Facilitation in the uptake of antigen-loaded nanocarriers, by the antigen-presenting cells and its subsequent presentation through the major histocompatibility complex molecules, leads to the activation of a cascade of immune responses. Further, such nanocarriers can be tailored to achieve the desired characteristics such as charge, size, size distribution, entrapment, and site-specificity through modifications in the composition of lipids and the selection of the appropriate method of preparation. This ultimately adds to its versatility as an effective vaccine delivery carrier. The current review focuses on the various lipid-based carriers that have been investigated to date as potential vaccine delivery systems, the factors that affect their efficacy, and their various methods of preparation. The emerging trends in lipid-based mRNA vaccines and lipid-based DNA vaccines have also been summarized.